Stress-Reactive Rumination, Negative Cognitive Style, and Stressors in Relationship to Depressive Symptoms in Non-Clinical Youth - Rood, Lea (Springer US, 2011)
The role of cognitive vulnerability in the development of depressive symptoms in youth might depend on age and gender. The current study examined cognitive vulnerability models in relationship to depressive symptoms from a developmental perspective. For that purpose, 805 youth (aged 10–18, 59.9% female) completed self-report measures. Stress-reactive rumination was strongly related to depressive symptoms. Negative cognitive style (i.e., tendency to make negative inferences) in the domains of achievement and appearance was more strongly and consistently related to depressive symptoms in girls compared to boys. Negative cognitive style in the interpersonal domain was positively related to depressive symptoms in both girls and boys, except in early adolescent girls reporting few stressors. To conclude, the cognitive vulnerability-stress interaction may be moderated by the combination of age and gender in youth, which may explain inconsistent findings so far. Current findings highlight the importance of taking into account domain specifity when examining models of depression in youth.